Internacionalização de parques tecnológicos: estudo de caso no Parque Tecnológico Itaipu-Brasil (PTI-BR) - Sousa, Marcelo Alves de (2019)
Technology parks should be quintuple helix interaction sites, involving academia, entrepreneurship, governments, investors, and society. Internationalizing parks gives visibility to their actions and facilitates the exchange of experiences globally, with comparative advantages. This article analyzes technology parks internationalization, with the Itaipu Technology Park-Brazil (PTI-BR) as a case study and suggests actions to internationalize technology parks. The data were collected in two questionnaires: one external, answered by 15 international relations authorities and one internal, answered by 11 professionals from the PTIBR ecosystem. International PTI-BR agreements and the literature on internationalization processes were analyzed as well. The results show that technology parks should focus on internationalization at home, prior to global internationalization. Parks should also analyze their vocation, regional development, innovation, entrepreneurship, cooperation and capacity building. Strategies should involve partner selection, review of strategic objectives, sustainability and structuring for internationalization, to make them references in the areas of their vocation, combined with their maintainers. This article also presents proposals to internationalize parks, and the research limitations. The main proposals to parks are to enhance their internationalization at home process and the relation with the quintuple helix; together with their maintainers, define their vocation, update their strategic planning; realizes VRIO and SWOT analysis and attracts more anchor institutions.